2020
DOI: 10.1093/aobpla/plaa002
|View full text |Cite
|
Sign up to set email alerts
|

Root flavonoids are related to enhanced AMF colonization of an invasive tree

Abstract: Arbuscular mycorrhizal fungi (AMF) are important mutualistic microbes in soil, which have capacity to form mutualistic associations with most land plants. Arbuscular mycorrhizal fungi play an important role in plant invasions and their interactions with invasive plants have received increasing attention. However, the chemical mechanisms underlying the interactions of AMF and invasive plants are still poorly understood. In this study we aim to test whether root secondary chemicals are related to enhanced AMF co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 71 publications
3
37
2
Order By: Relevance
“…Our previous study found higher concentrations of flavonoids but lower concentrations of tannins in roots of introduced populations of T. sebifera than in native populations [17] with quercetin and quercitrin being the main flavonoids [28,30]. In our pilot experiment, we only detected quercetin and quercitrin in root exudates but no other flavonoids.…”
Section: Collection Of Root Exudates and Flavonoids Analysis For Rootcontrasting
confidence: 44%
See 1 more Smart Citation
“…Our previous study found higher concentrations of flavonoids but lower concentrations of tannins in roots of introduced populations of T. sebifera than in native populations [17] with quercetin and quercitrin being the main flavonoids [28,30]. In our pilot experiment, we only detected quercetin and quercitrin in root exudates but no other flavonoids.…”
Section: Collection Of Root Exudates and Flavonoids Analysis For Rootcontrasting
confidence: 44%
“…Secondary chemicals are key root exudate components that could significantly affect AM fungal growth and colonization [17][18][19][20][21]. In particular, flavonoids, such as quercetin and quercitrin, have been reported to stimulate AM fungal spore germination and/or hyphal growth [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from impacting legume and bacterial interactions, flavanones (such as strigolactones) can positively influence the growth of ectomycorrhizal fungi and increase the colonization of AM fungi. For example, flavanones can enhance the germination of spores of ectomycorrhizal fungi in genera Pisolithus and Suillus as well as stimulate the production of symbiotic effector protein in the mushroom Laccaria bicolor ( Garcia et al, 2015 ; Pei et al, 2020 ). In contrast, the suppression of flavonoids and phenylpropanoid pathway secretion reduced the endophytes and ectomycorrhizal colonization of the maize and poplar roots, respectively ( Mehmood et al, 2020 ).…”
Section: Evidence and Model Framework For Interactions Between Plant mentioning
confidence: 99%
“…The fungal structures were stained with 0.05% Trypan blue for 24 h, after being washed in tap water five times. We then washed the Trypan blue out of the test roots and counted the hyphae at each of 300 gridline intersections on thirty 1 cm fine root segments, all from a single flowerpot, at 200 × microscope magnification [56][57][58].…”
Section: Arbuscular Mycorrhizal Fungi (Amf) Colonization Ratementioning
confidence: 99%